2016
DOI: 10.1038/nphoton.2016.227
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized instability in graded-index multimode fibres

Abstract: Multimode fibres (MMFs) are attracting interest for complex spatiotemporal dynamics, and for ultrafast fibre sources, imaging and telecommunications. This new interest is based on three key properties: their high spatiotemporal complexity (information capacity), the important role of disorder, and complex intermodal interactions. To date, phenomena in MMFs have been studied only in limiting cases where one or more of these properties can be neglected. Here we study MMFs in a regime in which all these elements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
151
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(158 citation statements)
references
References 55 publications
(113 reference statements)
6
151
1
Order By: Relevance
“…
Multimode optical fibres are enjoying a renewed attention, boosted by the urgent need to overcome the current capacity crunch of single-mode fibre systems and by recent advances in multimode complex nonlinear optics [1][2][3][4][5][6][7][8][9][10][11][12][13]. In this work, we demonstrate that standard multimode fibres can be used as ultrafast all-optical tool for transverse beam manipulation of high power laser pulses.
…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…
Multimode optical fibres are enjoying a renewed attention, boosted by the urgent need to overcome the current capacity crunch of single-mode fibre systems and by recent advances in multimode complex nonlinear optics [1][2][3][4][5][6][7][8][9][10][11][12][13]. In this work, we demonstrate that standard multimode fibres can be used as ultrafast all-optical tool for transverse beam manipulation of high power laser pulses.
…”
mentioning
confidence: 88%
“…MMFs could provide a solution to meet increasing demands of new breakthrough technologies for light control and manipulation in communications, high-power fibre lasers and metrology [1,2,16]. In fundamental physics, MMFs may provide a natural tool for investigating spatiotemporal soliton dynamics [5,6], and for unveiling new, exciting nonlinear phenomena [3,4,9,13].…”
mentioning
confidence: 99%
“…Multimode optical solitons [9], dispersive waves [10], geometrical parametric instabilities [11], spatial beam cleaning [12] and ultra-wide supercontinuum [13,14] may be counted among the major experimental advances reported over the last couple of years only. In particular, several papers have recently reported nonlinear beam reshaping and selfcleaning effects in multimode optical fibers with a parabolic refractive index profile (known as graded index or GRIN fibers) [11][12][13][14][15][16]. With these highly multimode fibers, light that is delivered as a random speckled beam at low powers was observed to evolve into a cleaned, almost Gaussian shaped beam at high power levels.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical explanation of the mechanism leading to the Kerr self-cleaning phenomenon is not yet completely clear, even though it can be well reproduced by means of the numerical integration of the (2 + 1 + 1) nonlinear Schrödinger (NLS) (or Gross-Pitaievski) propagation equation. The condensation of optical waves [6], as well as the nonlinear nonreciprocity of nonlinear mode coupling [12], and self-organized instability [15], have been proposed as possible mechanisms at play in the observed self-cleaning behavior. Beam self-cleaning was experimentally obtained in various experimental configurations involving different pump lasers, mostly at the 1 micrometer wavelength in the normal dispersion regime, with pulse durations ranging from femtoseconds [16] to nanoseconds [12], and with optical fibers of different diameters and from different manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…Quite remarkably, experiments of [7] revealed that the Kerr selfcleaning of the pump beam is frequency transferred across the entire spectrum of the GPI sidebands. Finally, for higher powers and fiber lengths, the GPI sidebands merge into a broadband SC as a result of the interplay of the Kerr effect and Raman scattering, and both effects cooperate with each other in reinforcing the wideband spatial beam cleaning [8,9,14,15]. In particular, the dependence of SC generation on a GRIN MMF as a function of pump power was experimentally studied in [8,15].…”
mentioning
confidence: 99%